The effects of interest rate on GDP growth and inflation rate using structural vector auto regressive (SVAR) model for Myanmar economy - Myint, Ohn Mar
bstract (This paper is interested in modeling and forecasting growth rate of the Gross Domestic Product (GDP) and Inflation Rate, using the Structural Vector Auto Regressive (SVAR) Model for the Myanmar Economy over the period from 2006 to 2015. One research interest of this paper is to measure the effect of Interest Rate on the GDP growth and Inflation Rate. For GDP and Inflation Rate, the SVAR model uses proxy variables such as the World Interest rate LIBOR, to simulate the impact of Central Bank policy on the Real Sector. Other variables such as the Money Supply and the Exports are also excluded. The results confirm a long-run equilibrium relationship between GDP, Inflation Interest rate, Money supply and Exports. In line with theoretical assumptions, the findings demonstrate that in the long run, GDP and inflation in Myanmar is related to the world Interest rate and the other factor. Our empirical findings suggest that the world rate plays a significant effect on GDP growth and a few effected on the Inflation. The results of this study show that the SVAR models possess high predictive ability specially in long time series where structural change of the economy).